Performance of Different Guava Cultivars under the Subtropical Condition of Himachal Pradesh - Kumari, Rashmi; Thakur, B. S.; Babita; Rimpika (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out at the Horticultural Regional Research Station, Dhaulakuan, (Sirmour District) of Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan during the year 2011-12. The trial was laid out on bearing guava trees in a Randomized Block Design. The treatments comprised of six cultivars/hybrids of guava viz., Hybrid-1, Hybrid-3, Allahabad Safeda, Hisar Safeda, L-49 and Lalit. In the present study, among tress characteristics, the highest plant height (3.30 m), trunk girth (5.28 cm) and shoot extension (24.90 cm) in Allahabad Safeda which was significantly higher than other cultivars. Flowering characteristics like duration of flowering (41 days) was also observed maximum in Allahabad Safeda. Cultivar Hisar Safeda was earliest to bloom (20thApril) followed by Lalit (21st April), Hybrid-1 (22nd April) and Hybrid-3 (23rdApril) and also earliest in full bloom (26th May) which was followed by again followed by Lalit and Hybrid-1(28th May). The longest maturity period (129 days) were also reported in Allahabad Safeda and Hybrid-1 was earliest in maturity (115 days) followed by Lalit (117 days) and Hybrid-3 (118 days). However, fruiting characteristics viz., maximum fruit set i.e. 73.40%, minimum fruit drop i.e. 42.80% and the highest yield of 10.20 k tree-1 was recorded in cv. L-49. On the basis of overall performance it was found that Allahabad Safeda was found most promising cultivar for subtropical condition of Himachal Pradesh.